Bilateral Mastectomy: dispute of PCA Morphine vs Bilateral erector spinae plane catheters-exploring best analgesic management for breast cancer surgery - Naidu, Durgalakshmi; Wong, Shee Ven; Mohamed Zaini, Mohamed Asri; Imam Supaat, Nuraiman; Abd Rashid, Nawal Wafa; Mohd Nasaruddin, Nur Asifa; Osman, Ariff; Abd Ghani, Muhamad Rasydan (Universiti Kebangsaan Malaysia, 2021)
Objectives: Surgical resection of the primary tumour with axillary dissection is a mainstream of breast cancer treatment. Many patients report moderate-to severe pain post-operatively. Acute post-surgical pain can cause chronic pain, and persistent use and over-prescription of opioids. The erector spinae plane block (ESPB) sufficiently blocks unilateral multi-dermatomal sensation from T1 to L3 and is a novel regional anaesthetic technique for effective analgesia after mastectomy, minimising opioid use. Methods: We study the analgesic efficacy of bilateral ESPB with continuous infusions with a bilateral rectus sheath block (RSB) in a patient undergoing bilateral mastectomy and left axillary clearance for left invasive breast carcinoma and right breast ductal carcinoma-in-situ, and incisional hernia repair. We discuss recommendations and best analgesic management after mastectomy. Results: The patient underwent ESPB using 20 ml of 0.2% Ropivacaine with catheter insertion bilaterally, and bilateral RSB with 20 ml of 0.2% Ropivacaine after the induction of general anaesthesia. Post-operatively, she was extubated, did not require intensive care, required no rescue opioids, had good pain control, and successful early mobilisation. Post-operative PCA Morphine usage was only for 24 hours. Conclusions: Regional anaesthesia for breast surgery reduces postoperative pain and opioid requirements, and, may be continued postoperatively using catheter techniques. The best analgesic technique for this patient could be PCA morphine alone, however, the combination of ESPB with continuous infusions, RSB and PCA morphine, provided excellent analgesia and allowed our patient to be discharged to the ward despite prolonged surgical hours. Patient experienced analgesic satisfaction, better night sleep, early ambulation, and recovery. Although the gold standard of analgesic techniques for bilateral mastectomy is bilateral Paravertebral Block, bilateral ESPB was performed as it is common in our centre. Despite the paucity of evidence, in the best hands, bilateral ESPB provided superior analgesia, as depicted in this case.